THE URGENCY OF COMMUNITY PARTICIPATION IN CONSERVATION AREA MANAGEMENT - Dr. Aullia Vivi Yulianingrum (Novateur Publications, 2023)
Land with customary land status, widely acknowledged in Indonesia since the Dutch colonial period, appears to be eradicated if the State chooses. This can be seen in Law No. 5 of 1960, Law No. 41 of 1999, and Law No. 11 of 1967, which State that customary land can be recognised as long as it still exists and does not conflict with national interests, although this is uncommon. Government Regulation of the Republic of Indonesia Number 21 of 1970 on Forest Concession Rights even explicitly states that the implementation of the rights of Customary Law Communities and their members to collect forest products based on a customary law regulation must be disciplined; thus, as not to interfere with the implementation of forest tenure. In the meantime, the performance of the people's right to obtain forest products has been halted in forest areas where forest exploitation occurs. This is the source of numerous hazards and conflicts in natural resource management, including the management of conservation areas.
Keywords: Community Participation; Conservation Area; Management